Revealing Direct and Indirect Strategies in Students’ Paraphrasing Completed by Verbal Report Protocol - Wicaksono, Banu; Lestari, Erma Rahayu (ICONELT, 2022)
This study investigates about students’ paraphrasing and the strategies they use. Eight students of the sixth semester of English department STKIP PGRI Jombang were voluntarily willing to enroll in the study. This study used case study as the approach in designing the research. The eight subjects did a paraphrasing task requiring them to do concurrent verbal report adapted from Ericsson and Simon (1993) while paraphrasing six sentences. Following this procedure the subjects then participated in a retrospective interview. The verbalized data and the interview were transcribed and analyzed qualitatively for identification of subject’s perception on paraphrasing and their strategies using adapted Oxford’s learning strategies (1990). The result of verbal report shows that there are 15 direct and indirect strategies of paraphrasing applied by the subjects, mostly cognitive and compensation strategies. Relating the two findings, quality of appropriate paraphrasing does not merely lies on the strategies the subjects applied but also their understanding and knowledge of paraphrasing as well as the acquisition of their English proficiency.